Employment or Exploitation? A Legal Comparative Study of Domestic Worker Protection in Singapore and Indonesia - Antony, Antony; Osmond, Agung Pratama; Ali Sabisi, Muhammad; Azlyn, Nurul; Rahmadani, Aini; Shahrullah, Rina Shahriyani (IHSA Institute, 2025)
This study aims to analyze the comparative legal protection systems for Domestic Workers (DWs) in Indonesia and Singapore, while highlighting the urgency of ratifying ILO Convention No. 189 as an international instrument to ensure decent work in the domestic sector. The research employs an empirical legal method, utilizing statutory, conceptual, and empirical approaches. The statutory approach involves reviewing national and international regulations related to labor and domestic worker protection. The data consist of primary data from observations and interviews, as well as secondary data from primary legal sources such as the 1945 Constitution of the Republic of Indonesia, Law No. 13 of 2003, the Draft Bill on Domestic Workers, the Employment of Foreign Manpower Act (EFMA), the Employment Act, and international instruments such as ILO Convention No. 189. The data are analyzed using descriptive-qualitative methods with deductive reasoning to identify normative and empirical gaps in the protection of domestic workers. The findings reveal that both Indonesia and Singapore have yet to provide comprehensive legal protection for domestic workers, particularly regarding formal employment status, basic rights, and access to justice. The ratification of ILO Convention No. 189 is considered crucial for both countries to improve national legal frameworks, raise protection standards, and enhance their diplomatic position and international reputation in upholding human rights and social justice.